Psychosocial Effect of Grade Retention of Learners in The Foundation Phase: A South African Case Study - Venketsamy, Roy (Islamic Early Childhood Education Study Program, Faculty of Tarbiyah and Education, UIN Sunan Kalijaga Yogyakarta, 2025)
Purpose – This study to explore teachers' perceptions on the impact of grade retention on the psychosocial wellbeing of Grade 1 learners in South Africa.Design/methods/approach – This study adopted a qualitative case study design within an interpretivist paradigm. It was grounded in Bronfenbrenner's Ecological Model as a theoretical framework. Data was collected through unobtrusive observation of four learners and a focus group interviews with the two teacher participants. An observation schedule was used by each teacher to record her observation and the semi-structured interview schedule was used during the focus group interview. The data was analysed using Creswell's 6 steps of data analysis using thematic approach. Through inductive process theme were identified and reported against. Ethical principles were adhered to as guided by the University of Pretoria's ethical guidelines for research. Approval for this study was obtained from the university.Findings – The findings revealed that grade retention affected young learners behaviours, emotions, social relationships and academic performance. Furthermore, retained learners exhibited signs of academic frustration, poor self-esteem, emotional outbursts and social challenges. Participants (teachers) shared ambivalent views regarding the department's retention policy. Teachers expressed mixed feelings about policy retention while other critiqued its emotional and social toll on learners.Research implications/limitations – The sample size was small with only two teachers and four learners, thus limiting the generalisability and transferability of the findings. A larger sample size with different grades may yield different result. Furthermore, geographically, the study was limited to only one province namely KwaZulu-Natal. Additionally, the study relied on teacher perspectives which may not fully represent the learner experiences or parental views.Practical implications – Some of the practical implications are policy revision — it is recommended that South African policymakers reconsider the retention policy by integrating psychosocial well-being criteria. Additionally, professional development is recommended so that teachers are equipped to recognize and manage the emotional impact of retention. An alternative intervention is to introduce support mechanisms such as remedial programs or peer support systems, rather than relying on retention. Finally, there should be a shift from an academic performance-centred curriculum to one that includes life skills and emotional intelligence development.Originality/value – This study offers a fresh perspective by highlighting the often-overlooked emotional consequences of grade retention. It adds value to the discourse by advocating for a more holistic approach to education that prioritizes psychosocial support alongside academic achievement. The study also contributes by proposing practical, systemic changes that can inform both policy and classroom practice in the South African context.Paper type Research paper